Silver nanoparticles (AgNPs) from plant extracts - Al-Zahrani, Samiyah Saeed (Journal of natural sciences, life and applied sciences, 2019)
Synthesis of silver nanoparticles have achieved a distinct focus with an emphasis on their biosynthesis using biological sources such as plants and microorganisms. since plant extracts provide best opportunity for improving green nanotechnology by creating a large array of nanoparticles with antimicrobial efficiency against a wide range of microorganisms such as pathogenic bacteria and plant pathogenic fungi, numerous studies have discussed the deep inroad of antibacterial effect of AgNPs. While there is a lack of studies that advent AgNPs efficiency against toxigenic fungi and control mycotoxins that associated with fungal contamination of food products. This review aimed to summarize the biological synthesis of AgNPs from different natural sources focusing on using this approach as antifungal agent against the most important toxigenic fungi to resolve the mycotoxins evolving issues which influence human and animals’ lives.